2020
DOI: 10.1186/s12978-020-00982-z
|View full text |Cite
|
Sign up to set email alerts
|

Induced abortion according to immigrants’ birthplace: a population-based cohort study

Abstract: Background Most abortions occur due to unintended pregnancy. Unintended pregnancies are linked to poor health outcomes. Canada receives immigrants from countries with disparate sexual and reproductive health contexts which may influence abortion rates post-migration. We examined the association between abortion and region of birth and birth order among Canadian immigrants. Methods We conducted a population-based person-years (PY) cohort study in Ontario, Canada using administrative immigration (1991–2012) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A population-based study using administrative immigration and healthcare data in Ontario found that induced abortion rates were two to five times higher among immigrants born in almost all regions of the world when compared to those born in the US, northern and western Europe, Australia and New Zealand. Additionally, immigrants from the Caribbean, West/ Middle/East Africa and South America were most likely to have an abortion (Wanigaratne et al 2020). US-based research has found that 8.4% of abortion patients are currently experiencing intimate partner violence (Saftlas et al 2010), and abortion is more common among women in poverty (Dehlendorf et al 2013).…”
Section: Disparities In Abortion Carementioning
confidence: 99%
“…A population-based study using administrative immigration and healthcare data in Ontario found that induced abortion rates were two to five times higher among immigrants born in almost all regions of the world when compared to those born in the US, northern and western Europe, Australia and New Zealand. Additionally, immigrants from the Caribbean, West/ Middle/East Africa and South America were most likely to have an abortion (Wanigaratne et al 2020). US-based research has found that 8.4% of abortion patients are currently experiencing intimate partner violence (Saftlas et al 2010), and abortion is more common among women in poverty (Dehlendorf et al 2013).…”
Section: Disparities In Abortion Carementioning
confidence: 99%
“…Moreover, in many migrant and refugee communities, taboos and stigma surround SRH [ 6 , 8 , 10 ], especially abortion [ 11 , 12 ]. Nevertheless, compared to women born in Australia and New Zealand, the United States, and Northern and Western Europe, immigrant women born in all world regions except Southern Africa were 2–5 times more likely to have an induced abortion [ 13 ]. Low SRH and contraceptive knowledge have been noted among migrant and refugee communities [ 7 ], which may increase the likelihood of unintended pregnancy and abortion.…”
Section: Introductionmentioning
confidence: 99%